Aspartate transaminase to platelet ratio index (APRI) but not FIB-5 or FIB-4 is accurate in ruling out significant fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) in an urban slum-dwelling population. Issue 1 (7th June 2019) - Kolhe, Kailash Marotrao; Amarapurkar, Anjali; Parikh, Pathik; Chaubal, Alisha; Chauhan, Shamsher; Khairnar, Harshad; Walke, Swapnil; Ingle, Meghraj; Pandey, Vikas; Shukla, Akash
Abstract : Background and aims: Non-invasive assessment of fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) is challenging, especially in resource-limited settings. MR or transient elastography and many patented serum scores are costly and not widely available. There are limited data on accuracy of serum-based fibrosis scores in urban slum-dwelling population, which is a unique group due to its dietary habits and socioeconomic environment. We did this study to compare the accuracy of serum-based fibrosis scores to rule out significant fibrosis (SF) in this population. Methods: Histological and clinical data of 100 consecutive urban slum-dwelling patients with NAFLD were analysed. Institutional ethics committee permission was taken. Aspartate transaminase (AST) to platelet ratio index (APRI), fibrosis-4 index (FIB-4) and FIB-5 scores were compared among those with non-significant fibrosis (METAVIR; F0 to F1; n=73) and SF (METAVIR; F2 to F4; n=27). Results: AST (IU/mL) (68.3±45.2 vs 23.9±10.9; p<0.0001), alanine transaminase (IU/mL) (76.4±36.8 vs 27.9±11.4; p<0.0001), FIB-4 (2.40±2.13 vs 0.85±0.52; p<0.0001) and APRI (1.18±0.92 vs 0.25±0.16; p<0.0001) were higher and platelets (100 000/mm 3 ) (1.8±0.8 vs 2.6±0.7; p<0.0001), albumin (g/dL) (3.4±0.50 vs 3.7±0.4; p<0.0001), alkaline phosphatase (IU/L) (60.9±10.2 vs 76.4±12.9; p<0.0001) and FIB-5 (−1.10±6.58 vs 3.79±4.25; p<0.0001) were lower in SF group. APRI had the best accuracy (area under the receiver operating characteristic curve=0.95) followed by FIB-4 (0.78) and FIB-5 (0.75) in ruling out SF. Conclusions: APRI but not FIB-5 or FIB-4 is accurate in ruling out SF in patients with NAFLD in an urban slum-dwelling population.